THE PHARMACEUTICAL AND ANALYTICAL STUDY OF PALASH KSHARA - Kasture Vikas V; Patil Vidula A; Mane Amitkumar S (International Journal of Ayurveda and Pharma Research, 2020)
Background: Kshara is an important dosage form mentioned in Ayurveda which is derived from plant ash. The Kshara have some similar properties like alkaline nature, water solubility, whitish color etc. Kshara are given advantage over all surgical and parasurgical measures as it can be used in thin, weak and patients who fears for surgery. Different herbs like Apamarga, Snuhi, Kadalipalasha are used to prepare Kshara either single or collectively in classical texts. Therapeutic use of Kshara of different herbs differs from each other hence analytical study of each Kshara is necessary. Aims & Objectives: In the present study preparation of Palash (Butea monosperma) kshara and analytical study is done to understand the characteristics of Palashkshara. Material & methods: The preparation of Kshara is a multistep procedure. In the present study preparation of Palasha Kshara is done according general method of preparation of Kshara mentioned in Sharangadhara Sanhita. Prepared Kshara is subjected to various Physico chemical analyses and results are concluded. Results: The Palash Kshara shows physical properties like whitish in color, pungent odor and soft in touch. Chemically it shows combination of Potassium, Phosphate and Sulphate along with other elements in traces. The present study gives the details of methodology and results of the pharmaceutical and analytical study of Palash Kshara.